Biocatalytic production of lactose ester catalysed by mica-based immobilised lipase - Zaidan, UH; Rahman, MBA; Othman, SS; Basri, M; Abdulmalek, E; Rahman, RNZRA; Salleh, AB (Elsevier Sci Ltd, 2024)
Indexed by Scopus/WOS